Physician’s Knowledge and Skill to Complete the Certificate of Cause of Death According to who Guidelines A Survey Among the Doctors of A Tertiary Care Hospital at Lahore\ - Muhammad Maqsood, Faizan Maqsood, M. Zahid Bashir, Muhammad Dawood, M. Kashif Butt, Umaima Manzoor Khattak (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The medical document certifying the cause of death provides vital data to develop health policies. In spite of very comprehensive guidelines issued by the WHO for thecompletion of death certificates; very few certificate arefound errorfree which might be due to lack of knowledge and practice on the part of physicians issuing that certificate.Purpose of this study is to assess the knowledge and competencies of a doctor in completing a death certificate. Methods: This study was cross-sectional. The population of this study was physicians of a tertiary care hospital of Lahore. A structured questionnaire along with a case scenario was given to 137 physicians having variable working experiences, performing in different clinical departments of a tertiary care hospital of Lahore.The participants were asked to complete the component of cause of death of the certificateonly. The percentage of omissions done by the doctors during the completion of said section was analyzed using the chi square test to establish the association between participant’s characteristics and their relevant responses. Results: Among 137participants working in different clinical departments of a Tertiary Care Hospital at Lahore, 89% were having less than 5 years’ experience and 11% having more than 5 years’ experience. 53% were qualified from public sector, 24% from private sector and 23% from foreign institutes. 77% doctors identified immediate cause of death incorrectly, 83 % did not identify and interpret underlying cause of death correctly; 90 % did notidentify contributory cause of death correctly. In46 % cases mechanism/mode of death was confused with the cause of death. Practical Implication: The correct completion of death certificates would provide an accurate and genuine mortality index essential for framing a national health policy. Conclusion: Physician’s knowledge and skill of completing the death certificates is very deficient and alarming which necessitate periodical and regular training of the physicians on completing the death certificates as per guidelines of the WHO to get an appropriate and valid health statistics effective for future public national health policies and strategies. Keywords (MeSH): Death certificate completion, Medical certification of cause of death, Physician’s knowledge, skill to complete death certificate, Mortality index